2011
DOI: 10.1051/0004-6361/201117074
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the “missing” low-mass stars in the S254-S258 star forming region by deep X-ray imaging

Abstract: Context. X-ray observations provide a very good way to reveal the population of young stars in star forming regions avoiding the biases introduced when selecting samples based on infrared excess. Aims. The aim of this study was to find an explanation for the remarkable morphology of the central part of the S254-S258 star forming complex, where a dense embedded cluster of very young stellar objects (S255-IR) is sandwiched between the two H ii regions S255 and S257. This interesting configuration had led to diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 62 publications
2
17
0
Order By: Relevance
“…By analogy with the two B0 stars investigated by Mucciarelli et al (2011), one expects about 300 low-mass pre-main sequence stars associated with HD 93521 if this stellar population follows a standard IMF 3 . We can now estimate what fraction of these low-mass objects would be detected with our X-ray observation and compare this to the actual number of sources in the field of view.…”
Section: The Surroundings Of Hd 93521mentioning
confidence: 99%
See 1 more Smart Citation
“…By analogy with the two B0 stars investigated by Mucciarelli et al (2011), one expects about 300 low-mass pre-main sequence stars associated with HD 93521 if this stellar population follows a standard IMF 3 . We can now estimate what fraction of these low-mass objects would be detected with our X-ray observation and compare this to the actual number of sources in the field of view.…”
Section: The Surroundings Of Hd 93521mentioning
confidence: 99%
“…The brightness of very young low-mass stars in the X-ray domain makes this the ideal energy range to distinguish between foreground or background field stars and genuine cluster members coeval with the massive stars. This technique was successfully applied to reveal the population of low-mass pre-main sequence (PMS) stars associated with two rather isolated B0 stars in the diffuse H ii regions S 255 and S 257 (Mucciarelli et al 2011).…”
Section: The Surroundings Of Hd 93521mentioning
confidence: 99%
“…The probability distribution of L t,c , called the XLF, is associated with the IMF due to the statistical link between X-ray luminosity and stellar mass M (e.g., Feigelson et al 1993;Preibisch et al 2005a;Telleschi et al 2007). The assumption of a "universal XLF" has been used to estimate total populations in young stellar clusters, including Cep B (Getman et al 2006), M 17 (Broos et al 2007), NGC 6357 (Wang et al 2007), Rosette (Wang et al 2008(Wang et al , 2009(Wang et al , 2010, W 40 (Kuhn et al 2010), Trumpler 15 (Wang et al 2011), Trumpler 16 (Wolk et al 2011, Sh 2-254/255/256/257/258 (Mucciarelli et al 2011), NGC 1893(Caramazza et al 2012, and IC 1396 (Getman et al 2012). During PMS stellar evolution, there is a weak relation between X-ray luminosity and age (e.g., Preibisch & Feigelson 2005;Pandey et al 2014); however, L t,c does not rapidly decline during the first 5 Myr, unlike the rapid decrease in bolometric luminosity L bol during PMS evolution along the Hayashi track.…”
Section: X-ray Luminosity Functionsmentioning
confidence: 99%
“…Mucciarelli et al (2011) continued their search for lowmass YSOs in the quiescent phase, with a deep Chandra X-ray observation, and found that the total number of YSOs was consistent with that expected from the Kroupa IMF (Kroupa 2001) scaled to the num- ber of ionizing sources. On the other hand, sequential star formation scenarios within the SFR have been proposed (Howard et al 1997;Minier et al 2007;Chavarría et al 2008;Bieging et al 2009;Wang et al 2011;Mucciarelli et al 2011). Circumstantial evidence, such as the age difference among HII regions, and the number ratio of YSOs at different evolutionary stages, indicate that star formation activity propagated from Sh 2-255 and 257 into the molecular clouds behind the HII bubbles.…”
Section: Introductionmentioning
confidence: 72%
“…Excess emission at IR wavelengths, particularly the mid-IR, is a useful membership selection criterion because a large fraction of PMS stars in young open clus- PMS stars are also known as X-ray emitting objects (Flaccomio et al 1999;Caramazza et al 2012;Hur et al 2012;Sung et al 2013b;Lim et al 2014b;Hur et al 2015). Mucciarelli et al (2011) made deep X-ray observations of these SFRs down to 0.5 M ⊙ with the Chandra X-ray observatory. The observations covered a 17 ′ × 17 ′ field, and detected a total of 364 X-ray sources.…”
Section: Membership Selectionmentioning
confidence: 99%